Masculinities and queer perspectives in transitional justice - Schulz, Philipp; Hamber, Brandon; Touquet, Heleen (Transitional justice., 2025)
"This book addresses the theory and practice of transitional justice through the lens of masculinities and queer perspectives. What and where are the intersections between masculinities and queer theories and frameworks for better understanding lived experiences of violence, justice and transitions? How can masculinities and queer perspectives enhance and 'complexify' our understandings of the intersections between gender, sexualities, armed conflict and (post-)conflict transitions? Incorporating masculinities and queer perspectives in transitional justice in tandem, and alongside one another, this book contributes empirically, conceptually and methodologically to an exploration of gender in processes of dealing with violent pasts. More specifically, and by taking on the task of combining, bringing into conversation and utilizing both masculinities and queer perspectives, the book aims to facilitate and contribute towards more inclusive, holistic and intersectional approaches of gender in dealing with the past. This book will appeal to scholars and students working in the areas of transitional justice, gender studies and socio-legal studies"--